Strategi Komunikasi Pemasaran Kedai Kopi Tambora Surabaya Dalam Meningkatkan Jumlah Pengunjung - Kusumawati, Yunita; Arkansyah , Moch Arkansyah (DIGICOM : Jurnal Komunikasi dan Media, 2024)
Coffee shop is a conversation in the community which is the attraction of a modern coffee shop. Coffe shop is a place to socialize for anyone who wants to get a relaxed atmosphere to discuss or just to greet never left behind by the times. Coffee is one of the drinks made from spices that has become a favorite drink around the world. Modern coffee shops are a topic of conversation in society and attract the attention of many people. Currently, the business in the field of coffee shops has developed with an interesting concept of sales and presentation, ranging from the design of the place to the menu offered. In this study using qualitative descriptive methods with data collection techniques through interviews with resource persons, observation and supported by data in the form of documentation. The results of this study found that the marketing communication applied by Kedai Tambora is through marketing carried out using Kedai Tambora's own Instagram social media or by marketing through paid promotions with one of the influencers in Surabaya.